Datacom equipment power trends and cooling applications (American Society of Heating, Refrigerating, and Air-Conditioning Engineers, 2012)
"Gives data center facility designers and manufacturers a clear understanding of their facilities' design needs and allows them to accurately predict the equipment loads their facilities will need to accommodate. Also includes air and liquid cooling options that may be considered"-- Provided by publisher.
Keywords: Electronic apparatus and appliances -- Cooling.; Telecommunication -- Equipment and supplies -- Cooling.; Air conditioning -- Design and construction.; Electronic data processing departments -- Design and construction.; elektronické knihy; electronic books